2019
DOI: 10.21873/invivo.11505
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Low Muscle Mass in Patients Undergoing Emergency Surgery for Colonic Perforation – A Single-center Experience

Abstract: Aim: The aim was to analyze the correlation between psoas muscle mass and mortality, as well as postoperative complications in patients treated for colonic perforation. Patients and Methods: A total of 46 patients met the study criteria. Patients were classified into an elderly (age, ≥75 years, n=24) and a younger group (age, <75 years, n=22). Background factors, postoperative data (including duration of hospital stay and discharge) were collected. The cross-sectional area of the psoas muscle area (PMA) was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Sarcopenia has been recognized as one of the key elements of frailty and is associated with poorer surgical outcomes. Pre‐operative sarcopenia as measured with CT data has been consistently demonstrated to be associated with higher post‐operative mortality after EL, 1–20 and further verified in systematic reviews and meta‐analyses 21–24 . One of the reported ways to quantify sarcopenia is via analysis of CT scans to measure the ratio of the cross‐sectional area of psoas muscle to the area of the L3 vertebral body.…”
Section: Introductionmentioning
confidence: 91%
“…Sarcopenia has been recognized as one of the key elements of frailty and is associated with poorer surgical outcomes. Pre‐operative sarcopenia as measured with CT data has been consistently demonstrated to be associated with higher post‐operative mortality after EL, 1–20 and further verified in systematic reviews and meta‐analyses 21–24 . One of the reported ways to quantify sarcopenia is via analysis of CT scans to measure the ratio of the cross‐sectional area of psoas muscle to the area of the L3 vertebral body.…”
Section: Introductionmentioning
confidence: 91%
“…Four studies were excluded because the abstract was only available and the full study was not retrievable in any database. Then, following a review of the full papers of the remaining hits, six were rejected for the following reasons: did not measure stoma incidence or complications with stomas [18], the study only looked at inguinal hernias [19], sarcopenia was not directly measured [20], surgery was only for colonic perforation [21], not all patients undergoing surgery received a stoma [4], and did not explore the complications of stomas [22] (see Table 1). Thus nine studies were finally included [23][24][25][26][27][28][29][30][31] and form the basis of this review.…”
Section: Overview Of All Included Studiesmentioning
confidence: 99%
“…Salem et al 12 Simpson et al 13 Simpson et al 11 Brandt et al 14 Imamura et al 10 Francomacaro et al 15 Trotter et al 16 Five of seven studies showed association between low muscle mass and increased mortality rates after emergency laparotomy surgery and the average 30-day mortality rate in the low muscle mass group as defined by low TPA was 26.6% (SD = 25.9) compared with 13.3% (SD = 15.8) in the control high TPA groups. Brandt et al 14 also showed a clear separation in mortality on day 30 after emergency laparotomy surgery between the investigated low and high muscle mass groups.…”
Section: Authorsmentioning
confidence: 99%